The Effect Of Servicescape And Promotion On Customer Revisit Intention, Mediated By Customer Satisfaction At 38 Coffee Lab - Christie, Christie; Shu, Efin (SEAN Institute, 2024)
38 COFFEE LAB experienced a decrease in sales and received complaints on Google reviews and from customers. People complained about the servicescape of 38 COFFEE LAB that the parking was not adequate, had a small space and a lot of noise in the cafe. The management did not do promotions on social media frequently and on other platforms. The purpose of this research is to find out the effect of servicescape (X1) and promotion (X2) on customer revisit intention (Y) with customer satisfaction (Z) as the intervening variable at 38 COFFEE LAB. This research uses a quantitative method. Data is collected by distributing the questionnaires using Google Forms. The population in this research are all customers of 38 COFFEE LAB, with a total sample of 100 people with a non-probability sampling technique which is convenience sampling. The results, all data has passed the normality test, heteroscedasticity test, and multicollinearity test. The result from the hypothesis test showed that store servicescape and promotion influence customer satisfaction and customer satisfaction influences customer revisit intention. However, servicescape and promotion do not significantly influence customers to revisit intention. In addition, customer satisfaction intervenes between servicescape and customer revisit intention and between promotion and customer revisit intention.